Breath : the new science of a lost art - Nestor, James (New York : PENGUIN LIFE, 2020)
-- Breath turns the conventional wisdom of what we thought we knew about our most basic biological function on its head. You will never breathe the same again.
P.B
Print version record.
Keywords: Breathing exercises; Respiration -- Popular works; Breathing exercises; Respiration; Electronic books; Electronic books; Popular works